Comparison of TNF-α and TGF-β Expression in Breast Cancer Tissues-with and without Axillary Lymph Node Metastasis - Tyasmara, Ayu; Sandhika, Willy (Indonesian Journal of Cancer, 2018)
Background: Breast carcinoma dynamics can be seen from the inflammatory mediator produced and some of expressed cytokine mediators mostly found in breast cancer tissues are TNF-α and TGF-β. This research analyzed TNF-α and TGF-β influence in axillary lymph nodes metastasis to prove the role of cytokines in breast cancer dynamics and to be taken as prognosis. Methods: This research used paraffin block of breast carcinoma in various stages of axillary lymph nodes metastasis and TNF-α and TGF-β antibody to observe the expressions. Result: There were significant differences in TNF-α expressions improvement with p < 0.05 in lymph nodes metastasis N1 (13.18%) and TNF-α expressions reduction in lymph nodes metastasis N2 (52.27%) and N3 (27.27%) compared with lymph nodes without metastasis (52.73%). There were no significant differences in TGF-β expressions of all N groups. Conclusion: The result stated that TNF-α cytokines can be used as biomarker independently predicting breast carcinoma prognosis and progressivity. ABSTRAKLatar Belakang: Dinamika karsinoma payudara tercermin dari mediator inflamasi yang dihasilkannya dan salah satu mediator sitokin yang terekspresi banyak pada jaringan tumor payudara adalah TNF-α and TGF-β. Kami menganalisis pengaruh TNF-α dan TGF-β pada metastasis kelenjar getah bening aksila untuk membuktikan peran sitokin dalam dinamika kanker payudara dan untuk dimanfaatkan sebagai alat prognosis. Metode: Penelitian ini menggunakan blok parafin karsinoma payudara pada berbagai stadium metastasis kelenjar getah bening aksila dan menggunakan antibodi TNF-α dan TGF-β untuk mendeteksi ekspresinya. Hasil: Hasil penelitian ini didapatkan perbedaan peningkatan ekspresi TNF-α yang signifikan dengan p < 0,05 pada metastasis kelenjar getah bening N1 (73,18%) dan penurunan ekspresi TNF-α pada metastasis kelenjar N2 (52,27%) dan N3 (27,27%) dibandingkan dengan tanpa metastasis (52,73%). Tidak ada perbedaan signifika n pada ekspresi TGF-β antar semua kelompok N. Kesimpulan: Hasil ini menyatakan sitokin TNF-α dapat dipakai sebagai biomarker untuk memprediksi progresifitas dan prognosis karsinoma payudara secara independen